2007
DOI: 10.1080/15389580601049968
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Driver Acceptance of the Honda Belt Reminder System

Abstract: Belt reminders in Honda as well as Ford vehicles are increasing. Although the increase is moderate (5.6 percentage points), on a national level it could have prevented at least 736 driver deaths in 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The Ford and Honda vehicles in the present study did not achieve 4% reductions, even before adjusting for vehicle age (Table 2). It may be that the estimates of Williams et al (2002) and Ferguson et al (2007) cannot be generalized to the entire driving population of the United States. Both studies were conducted at new car dealerships and were restricted to a single state.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The Ford and Honda vehicles in the present study did not achieve 4% reductions, even before adjusting for vehicle age (Table 2). It may be that the estimates of Williams et al (2002) and Ferguson et al (2007) cannot be generalized to the entire driving population of the United States. Both studies were conducted at new car dealerships and were restricted to a single state.…”
Section: Discussionmentioning
confidence: 93%
“…Williams et al (2002) reported that enhanced belt reminders in Ford vehicles increased driver seat belt use by 5 percentage points. Ferguson et al (2007) reported that enhanced belt reminders in Honda vehicles increased driver belt use by 6 percentage points. Theoretically a 5-6 percentage point increase in the belt use rate should reduce the number of driver deaths by approximately 4%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are similar results from the USA, where it has been reported that only approximately 4% of the drivers are against using a seat belt and 87% strongly agree that they would want to be wearing a seat belt in a crash (TRB, 2004). Ferguson et al (2006) found in interviews that nearly 90% of drivers having cars with seatbelt reminders would like one in their next car.…”
Section: Seat Belt Use As Key Element Of Safe Vehiclementioning
confidence: 99%
“…For cars with seat belt reminders, the seat belt use was found to be 98.9± 0.8%. Ferguson et al (2006) reported in 2006 a study done in the USA on the seat belt use in Honda cars. The observed the cars when the driver came to service points.…”
Section: Seat Belt Use As Key Element Of Safe Vehiclementioning
confidence: 99%